Australian driving restrictions: how well do neurologists know them?. Issue 9 (4th September 2018) - Caruana, Patricia; Hughes, Andrew R.; Lea, Rodney A.; Lueck, Christian J.
Abstract: Driving regulations are complex, particularly for neurological conditions, but accurate application of restrictions is important. This study was designed to investigate knowledge of the Austroads guidelines in medical students, neurological trainees and consultant neurologists using a questionnaire addressing both private and commercial licence restrictions related to five common neurological conditions, namely transient ischaemic attack (TIA), vasovagal episode, unwitnessed blackout, first epileptic seizure and benign paroxysmal positional vertigo. In total, 118 of the 120 returned responses could be analysed. Overall, 50% of all responses were correct. Respondents performed better for private than commercial licences, and consultants performed better than trainees and students. The highest proportion of correct answers was seen for vasovagal attack, and the lowest for TIA. In summary, knowledge of driving restrictions was relatively poor, and regular consultation of the guidelines is recommended. A larger study is warranted and increased education at both medical school and postgraduate levels should be considered.